2009
DOI: 10.1111/j.1365-2486.2008.01749.x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic regulation of gross methyl chloride and methyl bromide uptake from Alaskan Arctic tundra

Abstract: The Arctic tundra has been shown to be a potentially significant regional sink for methyl chloride (CH 3 Cl) and methyl bromide (CH 3 Br), although prior field studies were spatially and temporally limited, and did not include gross flux measurements. Here we compare net and gross CH 3 Cl and CH 3 Br fluxes in the northern coastal plain and continental interior. As expected, both regions were net sinks for CH 3 Cl and CH 3 Br. Gross uptake rates (À793 nmol CH 3 Cl m À2 day À1 and À20.3 nmol CH 3 Br m À2 day À1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
47
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 36 publications
4
47
1
Order By: Relevance
“…Likewise, the larger relative standard deviation in the CH 3 Cl flux measurements compared with the CH 3 Br flux measurements reflects the larger seasonal variation in the former than in the latter. The small net emission observed for CH 3 Cl on average across 6 sites and the whole growing season at Abisko is consistent with observations of emissions, on average, in Scottish wetlands (C. J. Hardarcre, unpublished data, 2009) and Irish peatlands [Dimmer et al, 2001] but in contrast to the average net CH 3 Cl uptakes of À637 (±610) ng m À2 h À1 [Rhew et al, 2007] and À1240 (±1350) ng m À2 h À1 [Teh et al, 2009] reported for the Alaskan tundra sites (again converting these authors' expressions of variability into standard deviations).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…Likewise, the larger relative standard deviation in the CH 3 Cl flux measurements compared with the CH 3 Br flux measurements reflects the larger seasonal variation in the former than in the latter. The small net emission observed for CH 3 Cl on average across 6 sites and the whole growing season at Abisko is consistent with observations of emissions, on average, in Scottish wetlands (C. J. Hardarcre, unpublished data, 2009) and Irish peatlands [Dimmer et al, 2001] but in contrast to the average net CH 3 Cl uptakes of À637 (±610) ng m À2 h À1 [Rhew et al, 2007] and À1240 (±1350) ng m À2 h À1 [Teh et al, 2009] reported for the Alaskan tundra sites (again converting these authors' expressions of variability into standard deviations).…”
Section: Discussionsupporting
confidence: 86%
“…Comparing this with the average flux in August 2008 of À13 (±19) ng m À2 h À1 (n = 16) shows there was no substantive inter-annual variation in CH 3 Br flux between these two years. In the Alaskan studies, the greater net uptakes of CH 3 Br and CH 3 Cl observed in 2006 than in 2005 was attributed to the higher soil temperatures in 2006 [Rhew et al, 2007;Teh et al, 2009].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Nevertheless, a fraction of each of these gases does reach the stratosphere (Salawitch et al 2005), where CH 3 Br is currently responsible for about 15% of the halogen-induced ozone loss and CH 3 Cl is responsible for about 13% (Butler 2000). Although the concentration of the methyl halides (CH 3 X) in the atmosphere is now well known, numerous natural sources and sinks have been identified, some quite recently-for example, fungi (Harper 1985), macroalgae (Laturnus 2001;Laturnus et al 1998;Manley and Dastoor 1987), peatlands (Khan et al 2012;Varner et al 1999), rice paddies (Khan et al 2011;Redeker et al 2002), salt marshes (Rhew et al 2000;Rhew and Maz eas 2010), oceans (Hu et al 2010;King et al 2000;Lu et al 2010;Singh et al 1983), tropical rain forests (Saito et al 2008), tundra (Rhew et al 2007;Teh et al 2009), fires (Andreae et al 1996), cattle (Williams et al 1999), and ants (Mead et al 2008). Thus, many questions and uncertainties in the global budgets of these gases remain (e.g., Butler 2000;Montzka et al 2011;Simmonds et al 2004;Yvon-Lewis et al 2009).…”
Section: Introductionmentioning
confidence: 99%